2018
DOI: 10.3390/rs10122069
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Mapping and Modeling Permafrost Thermal Dynamics across the Qinghai-Tibet Engineering Corridor, China Integrated with Remote Sensing

Abstract: Permafrost thermal conditions across the Qinghai–Tibet Engineering Corridor (QTEC) is of growing interest due to infrastructure development. Most modeling of the permafrost thermal regime has been conducted at coarser spatial resolution, which is not suitable for engineering construction in a warming climate. Here we model the spatial permafrost thermal dynamics across the QTEC from the 2010 to the 2060 using the ground thermal model. Soil properties are defined based on field measurements and ecosystem types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
(102 reference statements)
2
10
0
Order By: Relevance
“…For the Beiluhe basin areas, the relatively warm MAGTs ranged from −2.0 to 0 °C. The modeled MAGTs are consistent with the latest researches on MAGTs in QTP [58,59]. Comparing Figure 7 and Figure 14, we found that the subsiding regions are consistent with the ground with high MAGT value; the Tuotuohe and Beiluhe regions have experienced undergone serious ground deformation in recent years.…”
Section: Results and Analysissupporting
confidence: 87%
“…For the Beiluhe basin areas, the relatively warm MAGTs ranged from −2.0 to 0 °C. The modeled MAGTs are consistent with the latest researches on MAGTs in QTP [58,59]. Comparing Figure 7 and Figure 14, we found that the subsiding regions are consistent with the ground with high MAGT value; the Tuotuohe and Beiluhe regions have experienced undergone serious ground deformation in recent years.…”
Section: Results and Analysissupporting
confidence: 87%
“…The impacts that permafrost has on engineering constructions, infrastructure stability (e.g. along the Qinghai-Tibet Plateau Engineering Corridor [e.g., 14,15,16,17,18,19]) and on gravitational processes that can pose a hazard to communities [e.g., 20,21,12] makes the understanding of how its thermal regime responds to temperature increase very relevant. Moreover, little is known about the effects of permafrost degradation on hydrological processes, moisture and related ecosystem or carbon dynamics [e.g., 22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…By combining the WOFOST crop yield model and the WEP-L hydrological model, Jia et al [85] were able to estimate wheat yield 30 years into the future. To model future permafrost distribution and characteristics, Yin et al [169] and Luo et al [170] employed the specialized GIPL2 model, whereas Pastick et al [168] trained a DRT model with future climate data for a similar task. In general, however, next to OLS, machine learning methods are used much less frequently in this forecast model category.…”
Section: Categorization Of Forecasting Methodsmentioning
confidence: 99%
“…In general, however, next to OLS, machine learning methods are used much less frequently in this forecast model category. Of the 22 projection-based forecasting studies identified in this review, 15 were based on climate projections [78,85,130,131,134,142,[154][155][156][168][169][170]175,177,178], six on LULC projections [65,143,144,157,158,167], and one study on both [118].…”
Section: Categorization Of Forecasting Methodsmentioning
confidence: 99%
See 1 more Smart Citation